Development of Medical Record System Posyandu Taman Salak with Waterfall Method - Budisaputro, Crismantoro; Kusdwiadji, Agustinus; Villasari, Asasih (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
One form of ICT utilization in the health sector is a digital-based health application. Health applications are included in the National Health System (SKN). Posyandu is a form of health service effort that is managed by, for and from the community with the aim of facilitating access to basic health services for mothers and children. Posyandu Taman Salak is one of the health facilities available in Madiun City. The process of recording and processing data on all Posyandu Taman Salak activities is still done by handwriting in a report book. This causes cadres to have difficulty monitoring children's growth and development and are overwhelmed in preparing reports to the integrated health post supervisors. Based on the description of the problems at the Taman Salak Posyandu, it is necessary to develop a Posyandu medical record system to make it easier for Posyandu cadres to process Posyandu data, monitor child growth and development and make reports. The purpose of this study is to design and build a Posyandu Taman Salak medical record system using the Waterfall system development modeling. The design stages use DFD and ERD. The system has been completed based on the website and has conducted functional system testing with the result that all system functions can be run